Development of Online Courseware for Low-Achieving Special Education Students Learning Communication - Jumi, Miliana; Muhamad Adnan, Muhamad Hariz (Journal of Engineering, Technology, and Applied Science (JETAS), 2022)
In 2019, the government announced the Movement Control Order due to pandemic covid19. The situation leads to the closure of every school and premises to avoid the number of cases increasing. Every teacher conducts online classes where most of the students also facing difficulties in following the session. The study aims is to propose an online courseware for a lowly-achieving student based on communication subject. This study focuses on the development of courseware for form 1 of secondary school user. Lowly functional students are referring to students who unable to master the skills of reading, writing, and counting at a minimal level. The methodology used in this research is the evolutionary prototype with the integration of the SAM model, an instructional design model. A quantitative study was made among teachers and parents. As a result, a courseware called the BrightEdu were developed to help the children agree with the theoretical conclusions and research results of other authors.